2021
DOI: 10.1002/vetr.200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of enrofloxacin in rainbow trout (Oncorhynchus mykiss) following experimental challenge with Yersinia ruckeri

Abstract: Background: Use of enrofloxacin in trout farms is reported, especially for the treatment of yersiniosis, albeit various dosing regimens have been used. Therefore, optimal doses should be investigated. Methods: Five groups of 15 fish were challenged with Y. ruckeri. Two days later, three groups received feed containing enrofloxacin (ENR) at 1, 2.5 and 5 mg/kg fish respectively, during 7 days; one group received a single intraperitoneal injection of ENR at 10 mg/kg; and one group was left untreated. On day 15, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…As confirmed by previous studies, enrofloxacin, administered at a dose of 10 mg/kg of body weight, effectively controlled mortality and treated francisellosis in juvenile Nile tilapia (Oreochromis niloticus L.) [46]. Another study showed that feeding enrofloxacin at a dose of 2.5 mg/kg improved the survival rate of rainbow trout infected with Yersinia ruckeri [47].…”
Section: Discussionsupporting
confidence: 60%
“…As confirmed by previous studies, enrofloxacin, administered at a dose of 10 mg/kg of body weight, effectively controlled mortality and treated francisellosis in juvenile Nile tilapia (Oreochromis niloticus L.) [46]. Another study showed that feeding enrofloxacin at a dose of 2.5 mg/kg improved the survival rate of rainbow trout infected with Yersinia ruckeri [47].…”
Section: Discussionsupporting
confidence: 60%
“…(i) the potential non-linearity of PK absorption processes, e.g. with a saturable absorption at these doses; (ii) the toxicity at this dose range is not well known for fish; (iii) the palatability of food is probably a limiting factor (Hsu et al, 1994;Toften and Jobling, 1997), as already observed for sick animals (Rostang et al, 2021). Therefore, based on the MIC distribution of A. salmonicida of our study with ~70% of isolates having a MIC ≥ 0.25 µg/mL (figure 1), enrofloxacin does not seem to be an antibiotic of choice for the treatment against this bacterium.…”
Section: Pkpd Exploration and Dose Determinationmentioning
confidence: 99%
“…However, in the context of metaphylaxis, which is the most frequent use of antimicrobial in fish production (Lulijwa et al, 2020), the early initiation of an enrofloxacin treatment for the majority of fish would limit the influence of the infection on food intake and on the PK of enrofloxacin, while treating a rather low initial bacterial load. The use of other routes of administration, such as the intramuscular or the intraperitoneal route (as in vaccination campaigns) could be an alternative to the oral route, allowing better inter-individual reproducibility, and ensuring a sufficient dose to each diseased fish (Rostang et al, 2021).…”
Section: Limits Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used in aquaculture in view of its broad spectrum antibacterial activity and excellent pharmacokinetic characteristics (Lashev et al., 2015). ENR has been proved to have good antibacterial activity against most aquatic pathogens such as Aeromonas (Uney et al., 2021), Flavobacterium (Van Vliet et al., 2017), yersiniosis (Rostang et al., 2021), and Vibrio (Roque & Gomez‐Gil, 2003), and it is active at low concentrations, compared with other classes of antimicrobial agents (Langston et al., 2010). In aquatic animals, the main active metabolite of Enrofloxacin is ciprofloxacin (CIP).…”
Section: Introductionmentioning
confidence: 99%